Evidence for reduced export productivity following the Cretaceous/Paleogene mass extinction. (18th June 2015) - Esmeray‐Senlet, Selen; Wright, James D.; Olsson, Richard K.; Miller, Kenneth G.; Browning, James V.; Quan, Tracy M.
Abstract: The Cretaceous/Paleogene (K/Pg) mass extinction was associated with a collapse in the carbon isotopic (δ 13 C) gradient between planktonic and benthic foraminifera and a decrease in bulk carbonate δ 13 C values. These perturbations have been explained by several hypotheses: global collapse of primary productivity (Strangelove Ocean), greatly reduced export but not primary productivity (Living Ocean), little or no reduction in export productivity (Resilient Ocean), and geographic heterogeneity in the change of export productivity (Heterogeneous Ocean). We tested primary versus export productivity changes in the paleoshelf of New Jersey, where δ 13 C values and organic carbon accumulation rates can distinguish among different ocean responses. On the shelf, the K/Pg boundary is associated with a 2.5‰ δ 13 C decrease in bulk carbonate, a 0.8‰ δ 13 C decrease in organic carbon, a collapse of the surface to bottom δ 13 C gradient, and a drop in organic carbon accumulation rates. We interpret an early Danian 1.0‰ planktonic foraminiferal δ 13 C gradient, a 0.75‰ cross‐shelf benthic foraminiferal δ 13 C gradient, and a drop in carbon accumulation rates to reflect the presence of active primary but limited export productivity, consistent with the Living Ocean hypothesis. We evaluated interbasinal deep‐sea benthic foraminiferal δ 13 C gradients between the Pacific (Site 1210) and Atlantic (Site 1262) oceans as a proxy for changes in export productivity. The interbasinal δ 13 C gradient was reduced after the mass extinction, suggesting a reduction in global export productivity. Although our data support the Living Ocean hypothesis, evidence from paleoupwelling zones shows significant export productivity, indicating spatial heterogeneity in the wake of the K/Pg mass extinction (Heterogeneous Ocean). Key Points: Following the K/Pg, shelf surface‐bottom δ 13 C gradients and TOC accumulation rates collapsed Planktonic δ 13 C gradients were maintained and cross‐shelf δ 13 C gradients accentuated after the K/Pg Shelf and deep sea records indicate reduced export productivity (Living Ocean) after the K/Pg